Plasma generation of nanoparticles for high temperature composite applications. (22nd September 2009) - Luhrs, Claudia; Cheng, Lily; Phillips, Jonathan; Fanson, Paul
Results of this study suggest an inverse relationship between surface area (nanoparticles) and mechanical strength for a new class of ceramics, specifically nanoceramic particles manufactured in a plasma. In this study, the thermal stability of Ce-Zr, Zr-Al and tri-cationic Ce-Zr-Al ceramic oxide particles produced using the aerosol-through-plasma (A-T-P) technique was probed, and the tri-cationic particles were found to be the most sinter resistant in terms of fractional area loss with sinter time/temperature. The existence of an amorphous surface layer containing cations (e.g., Al+) immiscible with the core structure (e.g., Ce-Zr oxides) imparts stability. All findings are also consistent with an earlier model of nanoparticle formation in A-T-P: nanoparticles form via the shattering, of some or all of the hollow micron sized particles, caused by either thermal or mechanical stresses. Thus, bimodal distributions are only found for systems in which some, but not all, of the hollow micron scale particles shatter.